2012
DOI: 10.1007/s00421-012-2465-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact reduction during running: efficiency of simple acute interventions in recreational runners

Abstract: Running-related stress fractures have been associated with the overall impact intensity, which has recently been described through the loading rate (LR). Our purpose was to evaluate the effects of four acute interventions with specific focus on LR: wearing racing shoes (RACE), increasing step frequency by 10 % (FREQ), adopting a midfoot strike pattern (MIDFOOT) and combining these three interventions (COMBI). Nine rearfootstrike subjects performed five 5-min trials during which running kinetics, kinematics and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
72
3
6

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(90 citation statements)
references
References 44 publications
(67 reference statements)
9
72
3
6
Order By: Relevance
“…The increase in RFS prevalence midway through the race is not surprising when considering the greater muscular demands required of the plantar flexor muscles associated with non-RFS patterns compared with an RFS pattern (7). Further explanation for this shift in foot strike pattern comes from the finding of the higher post-race blood CK concentrations among those runners who were observed to use a MFS or FFS pattern compared with those who consistently used an RFS pattern.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The increase in RFS prevalence midway through the race is not surprising when considering the greater muscular demands required of the plantar flexor muscles associated with non-RFS patterns compared with an RFS pattern (7). Further explanation for this shift in foot strike pattern comes from the finding of the higher post-race blood CK concentrations among those runners who were observed to use a MFS or FFS pattern compared with those who consistently used an RFS pattern.…”
Section: Discussionmentioning
confidence: 90%
“…However, fatigue may also influence foot strike pattern as RFS prevalence has been observed to increase in marathoners through race progression (20). This shift from a FFS or MFS pattern to an RFS pattern may represent the result of fatigue of the plantar flexor muscles, whether because of greater eccentric loading with FFS or MFS patterns (7,37) or from higher preactivation of the plantar flexor muscles (23). To date, no studies have examined foot strike pattern during an ultramarathon to provide insight into whether fatigue or avoidance of impact affects foot strike patterns.…”
Section: Introductionmentioning
confidence: 94%
“…Finally, the participants adopted a significantly lower stride rate on the NMT, which may have reduced the neural load. While one research group has reported no changes in running root mean square EMG activity with increased stride rate (Giandolini et al, 2013), others have demonstrated increased iEMG activity of the vastus lateralis with higher cycling cadence (Bieuzen, Lepers, Vercruyssen, Hausswirth, & Brisswalter, 2007). Since iEMG activity was lower for all muscles measured on the NMT, the sum-iEMG measure accurately reflects the changes in recruitment of the lower limb, which was significantly lower and had a large effect size statistic.…”
Section: Discussionmentioning
confidence: 96%
“…On the NMT, running occurred on an incline and with a "mid-foot strike," compared to a flat surface with a "rear-foot strike" in overground. Indeed, tibialis anterior EMG activity is known to decrease across the entire stride cycle when changing from a "rear-foot strike" to a "mid-foot strike" due to decreased foot-ground impact shock (Giandolini et al, 2013). Adding to this, the rubber material of the NMT belt is designed to reduce the shock of impact.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, converting from a rearfoot to a forefoot or midfoot strike pattern has been promoted as a means to reduce the peak impact force, loading rate, and knee extensor moment. 5,8,12,18,19,38 In a case series, Cheung and Davis 12 reported that individuals with PFP exhibited improvements in pain after transitioning to a nonrearfoot strike pattern. Furthermore, barefoot running, which typically results in a forefoot or midfoot strike pattern, 5,25,46 has been reported to decrease peak PFJ stress by 12% in asymptomatic runners.…”
mentioning
confidence: 99%